1995
DOI: 10.1097/00000542-199509000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Agonists Modulate Release of Neurotransmitters in Bovine Trachealis Muscle

Abstract: We conclude that prejunctional kappa- and mu-opioid receptors attenuate the contractile response of isolated bovine trachealis muscle to EFS by inhibiting cholinergic neurotransmission. This effect is uniform throughout the trachealis muscle. delta-Opioid receptors are apparently not present in the bovine trachealis muscle. Caution must be used in extrapolating these results to the intact human. In this study little or no inhibitory effect of the opioids was observed at concentrations expected at airway recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Among the constrictor agents that may cause an asthmatic attack, there is ACh released from parasympathetic nerve endings near ASM, upon a reflex initiated at the vagus sensory receptors. The ACh release is, in turn, modulated by several pathways located within the nerve itself, including the M 2 -Gi pathway, which is activated by the ACh itself and promotes a negative feedback, the β 2 -Gs pathway [Brichetto et al 2003b], and opioid-receptor pathways [Zappi et al 1995].…”
Section: Physiology and Pharmacology Of Asm Contraction-relaxationmentioning
confidence: 99%
“…Among the constrictor agents that may cause an asthmatic attack, there is ACh released from parasympathetic nerve endings near ASM, upon a reflex initiated at the vagus sensory receptors. The ACh release is, in turn, modulated by several pathways located within the nerve itself, including the M 2 -Gi pathway, which is activated by the ACh itself and promotes a negative feedback, the β 2 -Gs pathway [Brichetto et al 2003b], and opioid-receptor pathways [Zappi et al 1995].…”
Section: Physiology and Pharmacology Of Asm Contraction-relaxationmentioning
confidence: 99%
“…Interactions between opioids and NMB agents have not been well described yet. Previous studies showed that opiates can inhibit ganglionic activity, cholinergic neurotransmission and neurogenic contractions in vitro 11 13 14. In rats, laudanosine was found to have a competitive interaction with mu-opioid receptors, resulting in a dose-dependent analgesic effect 12.…”
Section: Discussionmentioning
confidence: 97%
“…NMBAs can be potentiated by some drugs, such as systemic local anaesthetics7–10 and opioid mu agonists,11–15 which can decrease the onset and increase the duration of the NMB. In dogs, these drugs provide intraoperative analgesia and an anaesthetic-sparing effect16 17 that is beneficial to minimise the potential hypotensive effect induced by anaesthetic agents 6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So much of the data we have on nebulized morphine for terminal dyspnea, for example, either come from nonterminal populations 1 or even from nonhuman populations (i.e., cows). 2,3 As palliative care specialists, we then have to extrapolate and estimate whether the findings even apply to our patients.…”
mentioning
confidence: 99%